The Impact of Employee’s Empowerment on Organizational Citizenship Behavior in the Jordanian Ministries: Employees’ Perspective (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study investigates the influence of employees' empowerment on organizational citizenship behavior within the Jordanian ministries' centers. A systematic random sampling technique was employed to select a sample of 500 employees from 10 ministries. Three hundred and eighty-three viable questionnaires (76.6% of the samples) were examined and processed. The findings indicated a moderate level for both empowerment and citizenship behavior. A noteworthy positive impact of employees' empowerment on citizenship behavior was observed. Empowerment accounted for 46.5% of the variation in citizenship behavior. In conclusion, the study recommends reinforcing employees' empowerment and implementing measures to enhance citizenship behavior within the Jordanian ministries. Additionally, it underscores the importance of future research exploring mediating variables such as job satisfaction, organizational justice, and organizational commitment in understanding the relationship between employees' empowerment and citizenship behavior in the Jordanian public sector.
Keywords: Employees’ Empowerment; Organizational Justice; Organizational Citizenship Behavior; Jordanian Ministries